Applying the information-motivation-behavioral model to explore the influencing factors of self-management behavior among osteoporosis patients - Lhakpa Tsamlag; Huwen Wang; Qiuming Shen; Yue Shi; Shuxian Zhang; Ruijie Chang; Xiyu Liu; Tian Shen; Yong Cai (BMC, 2020)
Abstract Background The prevalence of osteoporosis (OP) is rapidly increasing. Healthy behaviors are crucial for the management of OP. Application of the information-motivation-behavioral skills (IMB) model has been verified in various chronic diseases, but this model has not been investigated for behavioral interventions among people with OP. This study aimed to examine factors influencing OP self-management behavior and their interaction paths based on the IMB model. Methods We conducted a cross-sectional study using a convenience sampling method in 20 community health service centers in Shanghai, China. Predictive relationships between IMB model variables and self-management behaviors were evaluated using an anonymous questionnaire. Structural equation modeling was used to test the IMB model. Results In total, 571 participants completed the questionnaire, of which 461 (80.7%) were female. Participants' mean age was 68.8 ± 10.1 years. Only 101 (17.7%) participants were classified as having better OP self-management behaviors. The model demonstrated the data had an acceptable fit. Paths from information to self-efficacy (β = 0.156, P < 0.001) and self-management behaviors (β = 0.236, P < 0.001), from health beliefs to self-efficacy (β = 0.266, P < 0.001), from medical system support to self-efficacy (β = 0.326, P < 0.001) and self-management behaviors (β = 0.230, P < 0.001), and from self-efficacy to self-management behaviors (β = 0.376, P < 0.001) were all significant and in the predicted direction. Conclusion This study validated the utility of the IMB model for OP self-management behaviors in this population. Middle-aged and older adult patients with OP have poor self-management behaviors. Enhanced knowledge about OP and is important for improving self-management behaviors.